Proceedings of the International Conference on Teacher Training and Education 2018 (ICTTE 2018) 2018
DOI: 10.2991/ictte-18.2018.55
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Students' Science Process Skill of Junior High School in Ngawi District in Material Classification and its Changes

Abstract: This study aims to determine the science process skills in material classification and its changes 7 th grade of junior high school in Ngawi. The method used in this research is quantitative descriptive. The sample of this research is taken by stratified random sampling technique. The initial profile of science process skills is analyzed from 51 state junior high schools in Ngawi with sampling proportion 10% in each strata. The sample which were used were 93 students from 3 schools which is include high catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
2
2
0
1
Order By: Relevance
“…The findings of this study are consistent with the literature, which indicates that multiplechoice questions are widely used to measure science process skills (Aydoğdu, 2017;Aydoğdu et al, 2012;Bahşi & Açıkgül Fırat, 2022;Ergül et al, 2011;Fathonah et al, 2018;Gill, 2019;Özçelik, 2019;Özgelen, 2012;Şensoy & Yıldırım, 2017;Şıvgın, 2019;Smith, 1995;Uysal & Cebesoy, 2022). However, there are also studies that utilized open-ended questions and activities, considering that the data collected only with multiple-choice questions would not be sufficient due to the nature of science process skills (Azizah et al, 2018;Çepni, 2004;Indri et al, 2022;Rezba et al, 1995;Rillero, 1998;Şahin et al, 2018;Serevina et al, 2018;Strong, 2013;Wu, 1994).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The findings of this study are consistent with the literature, which indicates that multiplechoice questions are widely used to measure science process skills (Aydoğdu, 2017;Aydoğdu et al, 2012;Bahşi & Açıkgül Fırat, 2022;Ergül et al, 2011;Fathonah et al, 2018;Gill, 2019;Özçelik, 2019;Özgelen, 2012;Şensoy & Yıldırım, 2017;Şıvgın, 2019;Smith, 1995;Uysal & Cebesoy, 2022). However, there are also studies that utilized open-ended questions and activities, considering that the data collected only with multiple-choice questions would not be sufficient due to the nature of science process skills (Azizah et al, 2018;Çepni, 2004;Indri et al, 2022;Rezba et al, 1995;Rillero, 1998;Şahin et al, 2018;Serevina et al, 2018;Strong, 2013;Wu, 1994).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the study's findings revealed that the devised online science process skills test could provide science educators with accurate and efficient results when assessing pupils' science Sarıoğlu, 2023 process skills. This is consistent with the literature, which highlights the importance of science process skills evaluation in science education (Fathonah et al, 2018;Gill, 2019;Özgelen, 2012;Şensoy & Yıldırım, 2017;Ülger, 2021). The test is also a web-based tool that is supported by videos that provide a more engaging and interactive experience for pupils.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Daya serap merupakan suatu tolak ukur seorang pendidik untuk mengetahui sejauh mana kemampuan seorang peserta didik dalam menguasai dan memahami suatu materi pembelajaran yang di ajarkan atau disampaikan dalam proses belajar mengajar (Aryantini et al, 2021;Meganingtyas et al, 2019). Daya Serap sangat berpengaruh pada hasil belajar siswa karena dengan siswa memiliki saya serap yang tinggi pada materi pembelajaran akan secara langsung membuat siswa memiliki hasil belajar yang baik (Aryantini et al, 2021;Fathonah et al, 2018). Oleh karena itu, daya serap yang baik sangat penting dimiliki oleh siswa dalam proses pembelajaran (Angelia Widyastuti & Widiana, 2020).…”
Section: Pendahuluanunclassified